Perwujudan Dan Implementasi Etika Dalam Pelayanan Publik Di Era Otonomi Daerah - Ni Wayan Sutiani (Jurnal Ilmiah Cakrawarti, 2019)
Public services both at the central and regional levels still do not apply Ethical values due todiverse understanding, not supported by adequate policies, contrary to local cultural values, and nonbinding.For this reason, the government needs to establish a policy on public service ethics in anintegrated and more operational manner that is able to create an understanding of central and regionalgovernment officials regarding the form of Public Service Ethics policy and applies to officials directlyrelated to the community and does not apply to officials who are not directly related to society. Thegovernment needs to develop and socialize a strategy for developing operational and integrated PublicService Ethics that accommodates the content of local culture and involves all existing public servicestakeholders, both in government offices and in private institutions.